O conceito de Técnica da Natureza na Crítica da Faculdade do Juízo de Kant - Leite, Oscar Vinícius Sillmann [UNESP] (2014)
This investigation aims to identify and to explicit the concept of technic of nature (Technik der Natur) in Kant's Critique of the Power of Judgment, looking to show its genesis, the background questions related to it and its relevance to the problems treated in this work. Our research moves around the problems posed by the empirical laws discovered in experience to the racional demands of systematicity and completeness of knowledge, which implies a conception of nature as a systematic whole. We look to show the role of the concept of technic of nature in grounding the possibility of scientific investigation, evidencing the transcendental assumptions that allow to coadunate the logic-formal aspects whereby the reflecting power of jugment produces a conceptual system from the material aspects of nature presented in experience.